DEVELOPMENT OF ANIMATED VIDEO LEARNING MEDIA USE APPLICATION CANVA STEAM BASED FOR IMPROVING LEARNING OUTCOMES STUDENTS - Ulfah, Nadia; Feri Tiona Pasaribu; Yelli Ramalisa (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This research is motivated by the lack of technology integration in learning which results in students having difficulty understanding the material, and leads to low learning outcomes. An innovation is needed to support the learning process which is expected to improve student learning outcomes. Therefore, the purpose of this study is to develop and assess the quality of learning media in the form of animated videos using the STEAM-based Canva application to improve student learning outcomes in the Enumeration Rules material. This research is a type of R&D development research with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects included one mathematics teacher and 35 students of class XI F1 of SMA Negeri 8 Muaro Jambi. The results showed that the developed media met the criteria of validity, practicality, and effectiveness. In terms of validation, the percentage of material feasibility reached 91.7% and the design reached 87.5%, which is classified as very valid. Meanwhile, the practicality of implementation , the teacher gave an assessment of 92% and students 90.9% which is also included in the very practical category. Meanwhile, the implementation of media effectiveness is seen from the student response questionnaire , which obtained a score of 88.42% in the very effective category. The results of the average difference test of student learning outcomes showed that the posttest score was better than the pretest score . The comparison results of the average N-Gain score of 0.65 with a percentage of 65% which is included in the fairly effective category. Thus, the STEAM-based animated video learning media using Canva is declared suitable for use in the learning process on the Enumeration Rules material for grade XI SMA because it meets the criteria of validity, practicality, and effectiveness. Penelitian ini dilatarbelakangi oleh kurangnya integrasi teknologi dalam pembelajaran, yang menyebabkan siswa kesulitan memahami materi dan mengakibatkan prestasi belajar rendah. Diperlukan inovasi untuk mendukung proses pembelajaran yang diharapkan dapat meningkatkan hasil belajar siswa. Oleh karena itu, tujuan dari penelitian ini adalah untuk mengembangkan dan menilai kualitas media pembelajaran berupa video animasi menggunakan aplikasi Canva berbasis pendekatan STEAM untuk meningkatkan hasil belajar siswa dengan topik Aturan Penghitungan. Penelitian ini merupakan jenis studi Penelitian dan Pengembangan (R&D) menggunakan model ADDIE, yang terdiri dari lima tahap: analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian antara lain seorang guru matematika dan 35 siswa dari Kelas XI F1 SMA Negeri 8 Muaro Jambi. Hasil penelitian menunjukkan bahwa media yang dikembangkan memenuhi kriteria validitas, praktis, dan efektif. Dari segi validasi, persentase kelayakan material mencapai 91,7% dan desainnya mencapai 87,5%, keduanya tergolong sangat valid. Mengenai kepraktisan, guru memberikan peringkat 92% dan siswa memberikan 90,9%, keduanya termasuk dalam kategori sangat praktis. Sementara itu, efektivitas media, berdasarkan kuesioner respon siswa, memperoleh skor sebesar 88,42%, dikategorikan sangat efektif. Hasil uji coba sampel independen hasil belajar siswa menunjukkan bahwa nilai pasca tes lebih baik daripada nilai pra-tes. Perbandingan rata-rata skor N-Gain adalah 0,65, setara dengan 65%, yang dikategorikan sebagai cukup efektif. Dengan demikian, media pembelajaran video animasi berbasis STEAM yang dikembangkan menggunakan Canva dianggap layak untuk digunakan dalam pengajaran topik Aturan Penghitungan untuk siswa SMA Kelas XI karena memenuhi kriteria validitas, kepraktisan, dan efektivitas